2020
DOI: 10.3390/jcm9020412
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Rare ALS Genetic Variants by Targeted Re-Sequencing Panel in Italian Patients: OPTN, VCP, and SQSTM1 Variants Account for 3% of Rare Genetic Forms

Abstract: Amyotrophic lateral sclerosis (ALS) is an adult-onset progressive neurodegenerative disease due to motor neuron loss variably associated with frontotemporal dementia (FTD). Next generation sequencing technology revealed an increasing number of rare and novel genetic variants and interpretation of their pathogenicity represents a major challange in the diagnosis of ALS. We selected 213 consecutive patients with sporadic or familial (16%) ALS, tested negative for SOD1, FUS, TARDBP, and C9orf72 mutations. To reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
6
23
1
Order By: Relevance
“…Comparing our results with those presented in previous reports [ 5 , 6 ], we can confirm that the majority of pathogenic variants identified are C9orf72 repeat expansions (39/59, 66%), followed by SOD1 (10/59, 17%) and TARDBP (8/59, 14%) variants.…”
Section: Applying the Acmg Standards And Guidelines For The Interpsupporting
confidence: 88%
See 3 more Smart Citations
“…Comparing our results with those presented in previous reports [ 5 , 6 ], we can confirm that the majority of pathogenic variants identified are C9orf72 repeat expansions (39/59, 66%), followed by SOD1 (10/59, 17%) and TARDBP (8/59, 14%) variants.…”
Section: Applying the Acmg Standards And Guidelines For The Interpsupporting
confidence: 88%
“…We were probably more conservative than other authors [ 5 ] in variant classification, since we found pathogenic or likely pathogenic variants only in 8 out 39 tested genes (21%). For instance, Pensato and colleagues identified these categories of variants in 12 out of 46 genes (26%) [ 5 ].…”
Section: Applying the Acmg Standards And Guidelines For The Interpcontrasting
confidence: 53%
See 2 more Smart Citations
“…Four major genes, chromosome 9 open reading frame 72 (C9orf72), superoxide dismutase 1 (SOD1), TAR DNA-binding protein (TARDBP), and fused in sarcoma (FUS) cover up to 60% of fALS and 10-13% of sALS cases [9]. Variants in other genes are found in < 1% of patients [10,11].…”
Section: Introductionmentioning
confidence: 99%